2015
DOI: 10.1124/jpet.115.227348
|View full text |Cite
|
Sign up to set email alerts
|

New Pyripyropene A Derivatives, Highly SOAT2-Selective Inhibitors, Improve Hypercholesterolemia and Atherosclerosis in Atherogenic Mouse Models

Abstract: Sterol O-acyltransferase 2 (SOAT2; also known as ACAT2) is considered as a new therapeutic target for the treatment or prevention of hypercholesterolemia and atherosclerosis. Fungal pyripyropene A (PPPA: 1,7,11-triacyl type), the first SOAT2-selective inhibitor, proved orally active in vivo using atherogenic mouse models. The purpose of the present study was to demonstrate that the PPPA derivatives (PRDs) prove more effective in the mouse models than PPPA. Among 196 semisynthetic PPPA derivatives, potent, SOAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Recent studies indicated that hepatic or intestinal SOAT2 might play a more important role in hypercholesterolemia or atherosclerosis [52, 53]. Accordingly, the studies on SOAT2-specific inhibitors, such as PPPA, revealed the potential of this class of compounds to treat hypercholesterolemia and atherosclerosis [54, 55]. In line with these findings, our results indicated that AVA treatment in the yolk did not, while PPPA treatment did, hindered the yolk consumption measurably in morphometry (Fig 8).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that hepatic or intestinal SOAT2 might play a more important role in hypercholesterolemia or atherosclerosis [52, 53]. Accordingly, the studies on SOAT2-specific inhibitors, such as PPPA, revealed the potential of this class of compounds to treat hypercholesterolemia and atherosclerosis [54, 55]. In line with these findings, our results indicated that AVA treatment in the yolk did not, while PPPA treatment did, hindered the yolk consumption measurably in morphometry (Fig 8).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, in this instance, the co-administration of ezetimibe would be an effective strategy for preventing this from happening and maximizing the benefit of the ERT. Alternatively, a case could be made for blunting re-esterification of this surplus UC within the liver using the new generation of selective SOAT2 inhibitors [63]. All the resources are available for exploring these clinically relevant questions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 7‐ O ‐ p ‐cyanobenzoyl derivative 2 , 1,11‐ O ‐ o ‐methylbenzylidene acetal derivative 3 , and 1,11‐ O ‐ o , o ‐dimethylbenzylidene acetal derivative 4 , which exhibited SOAT2 inhibitory activity and isozyme selectivity greater than those of 1 , have been developed (Figure and Table ). Furthermore, relative to 1 , these derivatives, particularly 3 , exhibited more potent in vivo efficacy …”
Section: Introductionmentioning
confidence: 95%